Analisis Kualitas Produk dan Efisiensi Energi Antara Mesin Daur Ulang Limbah Plastik Pemanas Band Heater dan Induksi - Luthfiyah, Almira; Rahayu, Theresia E.P.S.; Whiting Hayati, Sheptia; Bahri, Saipul; Nurhilal, Mohammad (P3M Politeknik Negeri Cilacap, 2024)
The melting process (extrusion) plays a key role in the recycling process of plastic waste into plastic pellets. This study aims to compare the recycling process of PET plastic waste between induction heating and band heater heating. The comparative analysis parameters are from the quality of the plastic pellets studied including water content, cadmium (Cd), and lead (Pb) based on SNI 8424:2017 and machine energy efficiency seen from electricity consumption and production speed. The results showed that the water content, cadmium metal content, and lead metal content of plastic pellets from the recycling process with an induction heating machine, namely 0.33%, 0.00049 ppm and 0.0633, were still far below the maximum quality standard limit even though the water content was higher than the plastic pellets produced by the band heater machine. The level of electricity consumption from the induction-heated machine was much lower with a higher production speed compared to the band heater-heated machine, namely 0.0849 kWh and 0.099 Kilogram Per Hour.